(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article extensively discusses the role, importance, and impact of psychological support in the process of medical rehabilitation on human health. The recovery process of the human body is closely related not only to medications and physiological procedures, but also to mental balance, emotional stability, and positive thinking. Therefore, psychological support during the rehabilitation period is considered a decisive factor in restoring the patient’s health. The article scientifically explains the main areas of psychological support, types of psychological support, and their impact on the patient’s condition. In particular, it is noted that trust between the doctor and the patient, love from loved ones, and motivation increase the patient’s recovery rate, reduce depression, and stress. Also, psychological support increases patients’ self-confidence and accelerates the process of returning to a healthy lifestyle. This article aims to inform medical professionals, psychologists, and students about the role of psychological factors in the process of medical rehabilitation and the importance of their proper organization. Psychological support, as an integral part of recovery, plays an important role in restoring a person’s physical and spiritual health.